Your place or mine? On the residence choice of young couples in Norway - Katrine V. Løken; Kjell Erik Lommerud; Shelly Lundberg (Institute for the Study of Labor (IZA), 2011)
Norwegian registry data is used to investigate the location decisions of a full population cohort of young adults as they complete their education, establish separate households and form their own families. We find that the labor market opportunities and family ties of both partners affect these location choices. Surprisingly, married men live significantly closer to their own parents than do married women, even if they have children, and this difference cannot be explained by differences in observed characteristics. The principal source of excess female distance from parents in this population is the relatively low mobility of men without a college degree, particularly in rural areas. Despite evidence that intergenerational resource flows, such as childcare and eldercare, are particularly important between women and their parents, the family connections of husbands appear to dominate the location decisions of less-educated married couples.
urn:nbn:de:101:1-201105173217
Keywords: J12; J16; J61; 330; intergenerational proximity; marriage; location decisions